2020
DOI: 10.2196/15094
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Women at Risk for Polycystic Ovary Syndrome Using a Mobile Health App: Virtual Tool Functionality Assessment

Abstract: Background Polycystic ovary syndrome (PCOS) is an endocrine disrupting disorder affecting about 10% of reproductive-aged women. PCOS diagnosis may be delayed several years and may require multiple physicians, resulting in lost time for risk-reducing interventions. Menstrual tracking apps are a potential tool to alert women of their risk while also prompting evaluation from a medical professional. Objective The primary objective of this study was to deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Sensitivity and specificity in our symptom checkers was between 75-100%. The PCOS symptom checker evaluated by Rodriguez et al 56 reported 12-25% false-positive cases and no false-negative out of 8 cases tested. Our PCOS symptom checker had no false-negatives and three false-positive cases (12.5%) out of 24 cases tested.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Sensitivity and specificity in our symptom checkers was between 75-100%. The PCOS symptom checker evaluated by Rodriguez et al 56 reported 12-25% false-positive cases and no false-negative out of 8 cases tested. Our PCOS symptom checker had no false-negatives and three false-positive cases (12.5%) out of 24 cases tested.…”
Section: Discussionmentioning
confidence: 98%
“…If changes were suggested, the case would then be reviewed, edited, and approved by a third GP who would finalise the case. Twenty-four cases were created for each condition, in line with other single-condition or single-system symptom checker evaluations [55][56][57][58] .…”
Section: Vignette Creation Review and Approvalmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluations of single-condition symptom checkers include a study of 12 web-based symptom checkers for COVID-19 [ 70 ] and a study of an app-based symptom checker for PCOS [ 62 ]. COVID-19 symptom checkers ranged widely in both sensitivity (14%-94%) and specificity (29%-100%), with only 4 symptom checkers having both sensitivity and specificity above 50% and 2 with both sensitivity and specificity above 75%.…”
Section: Discussionmentioning
confidence: 99%